2017
DOI: 10.1007/s00426-017-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Action effect features, but not anatomical features, determine the Backward Crosstalk Effect: evidence from crossed-hands experiments

Abstract: The Backward Crosstalk Effect (BCE) indicates that response features of Task 2 in a dual-task paradigm influence even Task 1 performance. However, it can be assumed that responses are represented with multiple features in the cognitive system. In this regard, Ideomotor Theory suggests action effects as one central response feature in human action control and an earlier study by Janczyk, Pfister, Hommel, and Kunde (Cognition 132: 30-43, 2014) already provided some evidence that action effects are a crucial dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…2). This sequential modulation also occurs with vocal responses in Task 1 or Task 2 (Renas, Durst, & Janczyk, 2017) and has been reported for preschool children (Janczyk, Büschelberger, & Herbort, 2017) as well as for older adults (Janczyk, Mittelstädt, & Wienrich, 2018).…”
Section: The Sequential Backward Crosstalk Effect In Dual Taskssupporting
confidence: 64%
See 1 more Smart Citation
“…2). This sequential modulation also occurs with vocal responses in Task 1 or Task 2 (Renas, Durst, & Janczyk, 2017) and has been reported for preschool children (Janczyk, Büschelberger, & Herbort, 2017) as well as for older adults (Janczyk, Mittelstädt, & Wienrich, 2018).…”
Section: The Sequential Backward Crosstalk Effect In Dual Taskssupporting
confidence: 64%
“…The examples reviewed above involved control adjustments of several kinds: Janczyk and colleagues observed a Gratton-like sequential modulation in a dual-task paradigm, in the form of reduced BCEs in dual-task pairs after R1-R2-incompatible relative to -compatible dual-task pairs (Janczyk, 2016;Janczyk et al, 2017;Janczyk, Mittelstädt, et al, 2018;Renas et al, 2017). Schuch and colleagues observed that control adjustments at the task level involve inhibition of the nolonger-relevant task during a task switch (Sexton & Cooper, 2017), as well as improved performance after task conflict (Schuch & Grange, 2015).…”
Section: What Kinds Of Control Adjustment?mentioning
confidence: 99%
“…Particularly, his data suggested that response selection of Task 1 is affected by response-related features of Task 2. Specifically, Task 1 performance was influenced by the response–response compatibility relation between the two tasks (as well as by the compatibility between the secondary response and the primary stimulus), a phenomenon referred to as backward crosstalk/compatibility effect (Hommel, 1998 ; see also Durst & Janczyk, 2018 , 2019 ; Hommel & Eglau, 2002 ; Huestegge, Pieczykolan, & Janczyk, 2018 ; Janczyk, Pfister, Hommel, & Kunde, 2014 ; Janczyk & Huestegge, 2017 ; Janczyk, Renas, & Durst, 2018 ; Renas, Durst, & Janczyk, 2018 ). This suggests that at least some aspect of response-related central processing (e.g., response activation) can occur in parallel.…”
Section: Parallel Central Processing Modelsmentioning
confidence: 99%
“…Interestingly, the BCE is modulated by contextual features (Fischer et al, 2014; Fischer & Hommel, 2012) and recent task history (Durst & Janczyk, 2019; Janczyk, 2016; Renas et al, 2018; Scherbaum et al, 2015) with a strong BCE following compatible trials and a smaller or even reversed BCE following incompatible trials (e.g., Janczyk, 2016). Such observations have been taken as evidence for enhanced “shielding” of the prioritized Task 1 from Task 2 influences (Fischer et al, 2014), triggered by the experience of conflict.…”
mentioning
confidence: 99%